Occurrence of the Sickle Pomfret Taractichthys steindachneri (Döderlein, 1883) in Palawan Waters with Notes on Pomfret Fishery in the Philippines - Dolorosa, Roger; Balisco, Rodulf Anthony; Yara, Archiel; Orqueza, John U. (Studia Ecologiae et Bioethicae, 2025)
Deep-sea species, although bizarre and odd-looking organisms, also warrant scientific and conservation attention. However, information on their occurrence and fishery throughout their distribution remains limited, hindering the development of effective conservation strategies. This paper contributes to addressing this gap by providing information on the occurrence of Sickle Pomfret Taractichthys steindachneri (Döderlein, 1883) in Palawan waters and notes on pomfret fishery in the Philippines. Two individuals were encountered for sale at the Puerto Princesa City New Public Market on 26 February 2023 and were photographed alongside a size reference. Standard (SL) and total lengths (TL) were measured using CPCe software, revealing significant sizes - 538.1 mm SL and 683.6 mm TL for the first individual, and 574.0 mm SL and 741.1 mm TL for the second, exceeding the previously recorded maximum lengths. Molecular sequencing further validated the species’ identity. Although seldom observed in the markets, the species are caught in deep trenches of the Sulu and West Philippine seas. In total, eight pomfret species are recorded in the Philippines, however, comprehensive information on the catch volume, fishing grounds, and other biological attributes of these species are needed to promote sustainable utilization and management.